The Impact of Human Resources Management Practices on Job Performance: The Case of Nurses at Siloam Lippo Village Hospital - Amelia, Ditta; Sijabat, Rosdiana (Jurnal Keperawatan Soedirman, 2020)
Human resources management has a huge role in increasinghospital performance. This study aimed to examine the effect of compensation, performance appraisal, recruitment and selection, teamwork, training, and development, on nurses' performance at the Siloam Lippo Village Hospital. A simple random sampling technique was used to collect data for this study. A questionnaire was distributed among 210 nurses at the hospital. The PLS-based Structural Equation Modeling (SEM) approach was used to check the impact of human resource management practices on job performance. The organizational commitment was used as a mediator variable on the relationship between human resource management practices and job performance. The results indicate that teamwork and organizational commitment have a significant impact on nurses' performance. This study also finds that compensation, performance appraisal, and training and development have a significant impact on organizational commitment, which leads to an increase in the nurses' performance. Organizational commitment significantly mediates the relationship between performance appraisal, teamwork, training and development, and job performance.